Empirical Evaluation of Kostiakov and Philip Infiltration Equation on Greyish Brown Regosol - M. Riza Januar; Nora H. Pandjaitan (PERTETA, 1999)
Inmation is important to note because it is related to potentialsurface run-08 jlood, erosion, water storage of soil, and stream discharge especially during dry season. However, because the infiltration equation is valid for certain condition of the land measured, it is important to collect infltartion data on all types of soil manually. This research is mainly to evaluate constants of infltration equation formulated by Kostiakov (constants K and n) and Philip (constants C and D) in relation with initial soil water content. The measurements are on vegetated soil and bare soil.